Case report: Spinal cord stimulation for pain relief in two patients with locally recurrent pelvic malignancy - Salem, Yousif; West, Charles T.; West, Malcolm; Yano, Hideaki; Fernandes, Paul; Vajramani, Girish; Mirnezami, Alexander (Frontiers in Oncology, 2024)
Introduction: Chronic cancer-related pain from locally recurrent infiltrative cancers within the bony confines of the pelvis is a devastating and hard to manage condition that can be refractory to many conventional pain management methods. Spinal cord stimulation (SCS) is an evolving and safe method of pain management and can be trialled in a quick and well-tolerated operation under local anaesthesia. To date, this has not been reported in the setting of locally recurrent inoperable pelvic cancers.In the present study, we report two cases of patients with severe back and lower limb pain resulting from recurrent anal and rectal cancers involving the right lumbar and sacral nerve roots as well as the bony sacrum, which severely affected quality of life and daily functioning.Discussion: Following successful SCS, effective pain relief was observed.conventional pain management in this challenging group of patients, especially if other available methods have been exhausted.